GENDER BIAS IN NEWS REPORTS A CASE OF REPORTING AFFAIR PRESENTED BY DETIK.COM AND NOVA.GRID.ID (BIAS GENDER DALAM TEKS BERITA STUDI TENTANG PEMBERITAAN KASUS PERSELINGKUHAN YANG DITAMPILKAN OLEH DETIK.COM DAN NOVA.GRID.ID) - Romiyati Falahul Alam (Universitas PGRI Sumatera Barat, 2020)
The misconception of gender concepts has an impact on discourse production. The discourse production tends to be discriminatory, in which the presence of women is more dominantly positioned as the object not as the subject. Recent news is about love affair case. The emergence of the term 'pelakor' (to mention women who are considered having an affair with a married man) is one form of discrimination in the production of discourse. This study aims to discover linguistic expression, men and women representation portrayed by detik.com and Nova.grid.id, and the socio cultural context contained in the news reports about love affair case. The datawere obtained through the documentation method and purposive sampling technique and analyzed using critical discourse analysis by Norman Fairclough.. The results show that in detik.com, men are more frequently mentioned than women. Meanwhile, in Nova.grid.id, the frequency of men and women mentioned in the news reports is more proportional. Gender bias based on vocabulary was revealed through the classification scheme in mentioningmen and women identity. Through the classification scheme, the text writer put men in an honorable position while women are considered to be dishonorable. On the other hand, gender bias seen based on transitivity shows that men are dominant fill the actor role while women tend to be placed as senser and sayer. This indicates that men are portrayed as being active while women are depicted as being more static and emotional. In the stage of explanation, the representation of men and women produced by detik.com and Nova.grid.id is influenced by patriarchal culture.